2020
DOI: 10.1063/1.5118762
|View full text |Cite
|
Sign up to set email alerts
|

Transverse magnetic field effects on spatial electron temperature distribution in a 13.56 MHz parallel plate capacitive discharge

Abstract: The effect of a transverse magnetic field on spatial electron temperature Te distribution along the line joining the center of capacitively driven rectangular discharge plates, operated at 13.56 MHz in a push-pull configuration, has been presented. It is found that the electron temperature distribution is almost uniform at low operating pressure (1 Pa). However, as the background pressure increases, the electron temperature tends to peak near the discharge plates. The overall magnitude in Te is also found to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
1
2
0
Order By: Relevance
“…As the electrons collide with the background gas atoms, the temperature in the central region becomes isotropic. As reported in our previous studies, Binwal et al [60], these effects are further enhanced when an external magnetic field is applied perpendicular to the discharge electrodes. And in our case, electrons would begin to drift parallel to the cylindrical surface in an E × B motion.…”
Section: Resultssupporting
confidence: 83%
“…As the electrons collide with the background gas atoms, the temperature in the central region becomes isotropic. As reported in our previous studies, Binwal et al [60], these effects are further enhanced when an external magnetic field is applied perpendicular to the discharge electrodes. And in our case, electrons would begin to drift parallel to the cylindrical surface in an E × B motion.…”
Section: Resultssupporting
confidence: 83%
“…There have been numerous studies on the effect of the magnetic field on electropositive discharge, especially for argon gas. It is found that spatial electron temperature distribution is affected by a transverse magnetic field at high pressure [26]. The electron kinetics were strongly affected by the uniform magnetic field and the nonlocal to the local transition of discharge characteristics was induced at stronger magnetic fields for high discharge frequencies [27].…”
Section: Introductionmentioning
confidence: 96%
“…[11][12][13][14][15] Although the dynamic behaviour of dust particles in a transverse magnetic field to the discharge axis was observed and analysed, these experiments were usually carried out in plasma with a high-frequency discharge. [16][17][18][19][20] However, the properties of micron particles in a stratified glow discharge in a crossed field are still unclear, since there is an absence of experimental work. It should be noted that many plasma devices are operated in ExB field configurations.…”
Section: Introductionmentioning
confidence: 99%